Issues in use of web-based information resources by public polytechnic students in southwestern Nigeria - John Adeboye Oyeboade; Adetutu Fatimo Talabi; Taiwo Hope Odeyemi; Mutiat Yewande Salvador; Kehinde Joy Makinde (Journal of Management and Science, 2023)
Many Nigerian polytechnic libraries seem not subscribe to or renew their subscriptions to Web-based Information Resources (WBIR) databases despite its increasing popularity in the academic world. Hence, the study was aimed to look into recurring issues in the use of WBIR by public polytechnic students in Southwestern Nigeria. Six public polytechnics out of the 16 offering Higher National Diploma (HND) programmemes were selected by stratified random sampling to reflect federal and stage polytechnics. Proportionate to size sampling technique was used to select 1,463 HND students. The instruments used were WBIR use for Academic Tasks (α=0.98), and Challenges of WBIR Use (α=0.84) scales. Data were analysed using proportionate and descriptive statistics. Majority of the respondents 709(51.1%) listed Google as the major search engine used. Others indicated a combination of Google and other search engines like Google, and Bing (71 or 5.1%), Chrome, Google, and Operamini (71 or 5.1%). Wikipedia (136 or 9.8%), and Myschool.com 55 (4.0%)are commondatabase/website used by the students.Challenges to WBIR use include high cost of accessibility (α=2.73) and download delay (α=2.64).Public polytechnic students in Southwestern Nigeria used web-based information resources, especially obtainable through Google search engine and Wikipedia.Information literacy programs at polytechnic libraries should not be taken lightly.